International Monetary Fund Annual Report 2020 Financial Statements. - International Monetary Fund. Secretary's Department (Washington, D.C. : International Monetary Fund, 2020)
The audited consolidated financial statements of the International Monetary Fund as of April 30, 2020 and 2019.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Public Administration; Public Sector Accounting and Audits